Karakteristik Mutu Pikel Jahe dengan Penambahan Ekstrak Bawang Dayak - Anggarkasih, Made Gayatri; Fatimah, Ai Imas Faidoh; Hapsari, Rianti Dyah; Nurwitri, CC; Qalbi, Rainatul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Processing ginger into pickles can provide added economic value and potentially become an export commodity. Ginger pickles are made by soaking ginger slices in a salt solution. Improving the quality of elephant ginger pickles can be done by adding natural dyes to have a pink color like Gari. Dayak onion extract can be used as a natural dye. This research aimed to determine the quality characteristics of ginger pickle with the addition of Dayak onion extract to the soaking medium at 7 dan 14 fermentation days and compare it with a salt solution soaking medium of various concentrations. This study is experimental research that used a Completely Randomized Design consisting of 6 treatments, namely a water-based and a Dayak onion extract-based soaking solution, each made with 5%, 7%, and 9% (w/v) salt concentration. The results showed (1) Adding Dayak Onion extract and variations of salt concentration in elephant ginger pickles had a significant effect on pH, and TPT and had no significant effect on the color and number of lactic acid bacteria); (2) Ginger pickles with a water-based 7% concentration salt solution (P2) most preferred treatment by the panelists.